Excavating the Ancestry of 'Globetrotting': New Perspectives on the Intersection of Racial Politics, Civil Rights Struggles and anti-Apartheid Crusades in US Track and Field from the 1920s through the 1980s. Issue 8 (15th July 2022) - Sikes, Michelle M.; Dyreson, Mark
ABSTRACT: During the twentieth century, systems of racial segregation flourished in both the United States and South Africa. Crusades for racial equality aimed at dismantling racial boundaries emerged in both nations. Sport played a key role in these endeavours. Drawing colour lines in athletic competitions reinforced ideologies of white supremacy while demanding racial equality in sporting contests fuelled campaigns challenging segregation. In an American culture that used athletes as globetrotting ambassadors to promote mythologies of exceptionalism, in particular aspirational but unrealized visions of racial equity, interchanges with South Africa highlighted the complex historical intersections between politics, race, and sport. From all-white US track and field tours of South Africa that began in the 1930s, to the key role that the leading American symbol of conquering colour lines, Jack Robinson, played in athletic affairs with South Africa, to American rebellions against anti-apartheid boycotts in the 1980s, this essay introduces a special issue on 'Excavating the Ancestry of "Globetrotting": New Perspectives on the Intersection of Racial Politics, Civil Rights Struggles and Anti-Apartheid Crusades in US Track and Field from the 1920s through the 1980s'.